2007
DOI: 10.1038/sj.bjc.6603948
|View full text |Cite
|
Sign up to set email alerts
|

Network-based analysis of calcium-binding protein genes identifies Grp94 as a target in human oral carcinogenesis

Abstract: To characterise Ca 2 þ -binding protein gene expression changes in oral squamous cell carcinomas (OSCCs), we compared the gene expression profiles in OSCC-derived cell lines with normal oral tissues. One hundred Ca 2 þ -binding protein genes differentially expressed in OSCCs were identified, and genetic pathways associated with expression changes were generated. Among genes mapped to the network with the highest significance, glucose-regulated protein 94 kDa (Grp94) was evaluated further for mRNA and protein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 44 publications
2
20
1
Order By: Relevance
“…Here, both molecules were found to be expressed in the cytoplasm of the gastric adenoma and carcinomas, carcinoma cell lines, consistent with their specific distribution in the ER. Statistically, GRP78 or GRP94 expression was highly expressed in gastric adenoma and adenocarcinoma in comparison with NNMs, in line with previous findings [9][10][11][12][13][14][15][16], suggesting that their up-regulated expression was involved in the pathogenesis of gastric carcinomas. Their concordant overexpression in gastric carcinomas might be due to the similar control elements of transcriptional control [23].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Here, both molecules were found to be expressed in the cytoplasm of the gastric adenoma and carcinomas, carcinoma cell lines, consistent with their specific distribution in the ER. Statistically, GRP78 or GRP94 expression was highly expressed in gastric adenoma and adenocarcinoma in comparison with NNMs, in line with previous findings [9][10][11][12][13][14][15][16], suggesting that their up-regulated expression was involved in the pathogenesis of gastric carcinomas. Their concordant overexpression in gastric carcinomas might be due to the similar control elements of transcriptional control [23].…”
Section: Discussionsupporting
confidence: 90%
“…Aberrant GRPs' expression and activation may play an important role in cancer development and progression [6,[9][10][11][12][13][14][15][16]. In the present study, overexpression of GRP78 and GRP94 was found to closely link to the tumor size, depth of invasion, lymphatic or venous invasion, and UICC staging, indicating that their overexpression might have impact on the growth, invasion, metastasis, and progression of gastric carcinomas and can be used to indicate the aggressive behaviors of carcinomas.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This finding is contradictory to several reports in the literature showing increased GRP94 expression in a variety of malignant tumors or cancer cell lines, such as breast (23), oral (24), lung (25), gastric (26), esophageal (27) and colonic carcinomas (28). Using immunohistochemistry we observed that GRP94 was absent or weakly present in ductal cells but strongly present in acinar cells in chronic pancreatitis and normal pancreatic tissues.…”
Section: Discussioncontrasting
confidence: 56%
“…If we can make use of biomarkers to detect oral cancer at their early stage it will be a promising way to help patients and lower the mortality. studies have reported that several single genes play an important role in the carcinogenesis of olK, such as p53 (24), , tumor amplified and overexpressed sequence 1 (TAOS1) (26), major histocompatibility complex class I-related chain A (MIcA) (27), ras association domain family (rAssF) (28), ataxia telangiectasia mutated (AtM) (29), Melanoma-associated antigens-A1-A6 (MAge-A1-A6) and Melanoma-associated antigen-A12 (MAge-A12) (30), urinary-type plasminogen activator and upA receptor (upA-upAr) (31), cytokeratin 17 (ck17) (32), glucose-regulated protein 94 kDa (grp94) (33) and so on. In the precancerous oral lesions, survivin (34), MMp-1 and MMp-9 (35) were found to be up-regulated compared with normal oral tissue, while rAr-β2 (36), Kai1 (37) and FHI (38) were inhibited.…”
Section: Discussionmentioning
confidence: 99%